Shared Sensemaking: Enhancing the Value of Collaborative Web Search Tools - Morris, Meredith Ringel; Amershi, Saleema (Proceedings of CHI 2008, 2008)
Current Web search tools, such as browsers and search engine sites, are designed for a single user, working alone. However, users frequently need to collaborate on information-finding tasks; for example, students often work together in groups on homework assignments. To address this need, we have prototyped and evaluated several collaborative web search tools (S3, SearchTogether, and CoSearch) that enable synchronous, asynchronous, colocated, and remote collaboration on Web search tasks. Such tools could be further enhanced by enabling collaborators to transition from shared Web searching to joint sensemaking activities; the products of this sensemaking could in turn be offered to others in response to their queries, enabling a community-level search/sensemaking cycle.